Moringa oleifera Oil Nutritional and Safety Impact on Deep-Fried Potatoes - Boukandoul, Silia; Zaidi, Farid; Santos, Carla S. P.; Casal, Susana (Foods, 2023)
Aiming to understand the nutritional impact of Moringa oleifera oil (MOO) on the quality of fried potatoes as consumed, a frying study using intermittent frying at 180 °C was conducted over 5 days, with a total heating time of 15 h, against olive (OO) and sunflower (SFO) oils. Additionally, due to MOO’s higher costs, a SFO/MOO blend (80/20 w/w) was tested. With similar fat incorporation and moisture contents, potato lipid composition revealed the impact of oil oxidation over the frying time, gradually decreasing the content of unsaturated fatty acids and antioxidants, including vitamin E, carotenoids and ascorbic acid, and increasing the incorporation of trans fatty acids (TFAs) and volatile aldehydes. When the potatoes fried at the ninth hour of heating are compared, MOO and OO were still able to protect potato ascorbic acid better than SFO, due to the low oxidative stress imposed by their fatty-acid composition. SFO, on the contrary, with linoleic acid as the main fatty acid, and despite its higher content of vitamin E, demonstrated higher oxidative stress and increased incorporation of alkenals and alkadienals. Acrylamide content was generally low, as were the trans fatty acids formed and incorporated with frying time, with MOO fried potatoes having lower amounts of all these process contaminants. Interestingly, the blend SFO/MOO (80/20 w/w) doubled the amount of vitamin E in fried potatoes when compared with SFO alone, increased the ascorbic acid protection and reduced by half the amounts of volatile aldehydes, indicative of an efficient reduction of the oxidative status of the SFO-fried potatoes, with benefits to the consumer from a health point of view.